Teacher Agency in Micro-Curriculum Design: Enhancing Student Achievement through an Interest-Based Arabic Learning Program - Mashlahatul Hidayah; Nur Ahid (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
Research on Arabic language education has largely focused on instructional strategies and curriculum implementation, while limited attention has been given to teachers’ agency in designing micro-curricula within interest-based learning programs. This study explores how teachers design and enact micro-curricula and how these practices contribute to student engagement and achievement in an interest-based Arabic learning program. Employing a qualitative case study, the research involved a program coordinator, two supervising teachers, and seven students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using thematic procedures adapted from Creswell’s qualitative framework. The findings indicate that teachers exercise substantial agency as micro-curriculum designers by developing learning content aligned with students’ interests, including af‘āl yaumiyyah, ibārah qaṣīrah, muḥādathah, khiṭābah, and qirā’at al-akhbār. The curriculum is enacted through communicative pedagogies, particularly the direct method, drills, and collaborative learning activities tailored to learners’ characteristics. These practices foster students’ communicative competence, self-confidence, and motivation to use Arabic actively. The effectiveness of the program is reflected in students’ success in securing thirteen awards in district- and provincial-level Arabic competitions. This study contributes to the literature by conceptualizing teachers as active micro-curriculum designers whose pedagogical decisions shape learner engagement and achievement in specialized Arabic learning contexts.